SISTEM INFORMASI BERBASIS WEB PADA ARSIP SURAT MASUK DAN PENOMORAN SURAT KELUAR DI SUBBAGIAN UMUM DINAS PENDIDIKAN PROVINSI DKI JAKARTA - Avikatria Cahyaningrum (2022)
The archive is one of the supporting parts in an activity in a government agency because it will be packaged in a long time. Archives need to be controlled properly in order to facilitate the search process when the archive is needed. The Secretariat of the General Subdivision at the DKI Jakarta Provincial Education Office collects data on the numbering of outgoing letters using thick books and stores the disposition of incoming letters which are still stored in file cabinets. These activities can lead to data inconsistencies in the preparation of outgoing mail reports and the scattering of disposition archives while being borrowed. So, we need a system that has been computerized so that it can help deal with problems in managing the archive. This system is designed using Waterfall and identified using PIECES, in modeling the system illustrated with Unified Modeling Language or UML, with the language used to translate into machine language is PHP, and the database used is MySQL. The results will be obtained in the form of a computerized web-based archive information system application, so that it will help manage archives, downloads, and reports. This software can only be accessed by the internal division of the DKI Jakarta Provincial Education Office Secretariat.